Tales from a not-so-popular party girl - Russell, Rachel Renée (Dork diaries, 2010)
Nikki's diary describes a frightful Halloween, on which she helps with her sister's ballet class party at the same time she is Brandon's date for their middle school Halloween dance, where she has promised to spend the evening with her two best friends.